Si-Miao-Yong-An Decoction Protects Against Cardiac Hypertrophy and Dysfunction by Inhibiting Platelet Aggregation and Activation - Su, Congping; Wang, Qing; Zhang, Huimin; Jiao, Wenchao; Luo, Hui; Li, Lin; Chen, Xiangyang; Liu, Bin; Yu, Xue; Li, Sen; Wang, Wei; Guo, Shuzhen (Frontiers in Pharmacology, 2019)
Objective The aim of this study was to determine whether SMYAD could ameliorate pressure overload-induced heart hypertrophy and its mechanisms. Methods C57BL/6 mice were subjected to either sham or transverse aortic constriction (TAC) surgery to induce heart hypertrophy. SMYAD (14.85g/kg/d, po) or Captopril (16.5mg/kg/d, po) was administered to the mice for 4 weeks. Cardiac function was evaluated based on echocardiography. Histological and biochemical examination were also performed by HE staining. Protein expression of CD41, CD61, P-selectin were measured with western blotting and immunohistochemistry. Results Four weeks after transverse aortic constriction, mice developed exaggerated cardiac hypertrophy and demonstrated a strong decrease in left ventricular ejection fraction (LVEF) compared with sham (29.9±9.3% versus 66.0±9.9%; P<0.001). Conversely, SMYAD improved cardiac dysfunction with a preserved LVEF (66.5±17.2%; P<0.001). The same changes were observed in left ventricular posterior wall, left ventricular volume and left ventricular internal diameter. The ratio of heart weight to body weight was also significantly increased 4 weeks after TAC, which could be rescued by SMYAD. Furthermore, western blot and immunohistochemistry indicated that the protein expressions of platelet aggregation marker (CD41, CD61) and platelet activation marker (P-selectin) were significantly higher compared to control. These pathological alterations in TAC-mice were significantly ameliorated or blocked by SMYAD administration. Conclusions Our results suggested that SMYAD exerted its effect by inhibiting platelet aggregation and activation as revealed by CD41/CD61/P-selectin up-regulation. Activation of the platelet might contribute to the therapeutic effects of SMYAD in failing heart.